2002
DOI: 10.1093/geront/42.1.39
|View full text |Cite
|
Sign up to set email alerts
|

A Social–Cognitive Model to Predict the Use of Assistive Devices for Mobility and Self-Care in Elderly People

Abstract: This study suggests that a social-cognitive model of human behavior can be helpful in explaining the use of ADs. The model can suggest measures to be developed aiming to improve the introduction of ADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 19 publications
0
49
0
1
Order By: Relevance
“…GSE may also be useful to select those patients who may be helped by counselling or cognitive behaviour therapy along the disease progression as ALS patients: Roelands et al [33] have found that self-efficacy is related to a greater predisposition to accept and use ADs in elderly patients with problems of self-care and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…GSE may also be useful to select those patients who may be helped by counselling or cognitive behaviour therapy along the disease progression as ALS patients: Roelands et al [33] have found that self-efficacy is related to a greater predisposition to accept and use ADs in elderly patients with problems of self-care and mobility.…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for the lack of a relationship is that in this case, older adults depend on their own beliefs and judgment. Roelands et al (2002) study used 491 community-dwelling elderly between 70 to 89 years of age to measure the use of assistive devices. Self-efficacy (self-efficacy was used in this study instead of PBC) (β=.47, p≤.001) showed a stronger significant prediction power for intention than attitude (β=.17, p≤.001) and subjective norm (β=.01, p≤.05).…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Our study results demonstrate that some subscales exhibit better psychometric properties than others, and thus, these subscales deserve further consideration for use as a screening tool. Other instruments, such as those developed by Roelands and colleagues measuring self-efficacy and intention [6], can also be explored for use as screening tools because they may be administered before actual assistive device use. Finally, because adherence requires active involvement of the patient in managing the device, initial patient screening may be combined with subsequent training strategies that are based on psychosocial factors associated with compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The QUEST is designed to measure satisfaction with a broad range of assistive technology and asks respondents how satisfied they are with specific features such as weight, height, length, width, and some characteristics of the services related to the device, i.e., repairs and servicing [5]. In another study, Roelands and colleagues developed separate subscales for community-dwelling older adults living in Belgium to measure awareness, possession and use of assistive devices, attitudes toward use, self-efficacy, and intention to use assistive devices [6].…”
Section: Introductionmentioning
confidence: 99%